Resin composition
By introducing monofunctional epoxy compounds into the ethylene-vinyl alcohol copolymer and treating them with specific catalysts and chelating agents, the transparency and melt stability problems of EVOH after plasticization were solved, and modified EVOH with excellent properties was prepared, suitable for multilayer films and composite materials.
Patent Information
- Application Number
- JP2023117618
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2021-12-24
- Filing Date
- 2023-07-19
- Publication Date
- 2025-02-10
- Estimated Expiration
- 2042-12-23
AI Technical Summary
In the prior art, the transparency of ethylene-vinyl alcohol copolymer (EVOH) decreases after plasticization, and the melt stability and torque fluctuate greatly during long-term melt processing, resulting in color change problems.
The ethanone solution containing zinc ions and sulfonate ions is used as a catalyst and melt blended with monofunctional epoxy compounds in an extruder to prepare modified EVOH. By controlling the amount of catalyst and neutralizing residual catalytic activity with chelating agents, melt stability and transparency are improved.
The prepared modified EVOH has excellent gas barrier properties, stretchability and melt stability, reducing catalyst residues and avoiding color change, and is suitable for multilayer films and composite materials.
Smart Images

Figure 0007628585000013 
Figure 0007628585000001 
Figure 0007628585000002
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for producing a modified ethylene-vinyl alcohol copolymer. The present invention also relates to a method for producing a resin composition containing the copolymer. The present invention further relates to a method for producing mixed pellets containing pellets of the copolymer. The present invention also relates to a resin composition containing a modified ethylene-vinyl alcohol copolymer. [Background technology]
[0002] Ethylene-vinyl alcohol copolymer (hereinafter sometimes abbreviated as EVOH) has excellent transparency and gas barrier properties, but has the drawback of lacking stretchability and flex resistance. To improve this drawback, a method is known in which EVOH is blended with a flexible resin such as an ethylene-vinyl acetate copolymer or an ethylene-propylene copolymer. However, this method has the drawback of greatly reducing transparency.
[0003] Patent Document 1 describes a method for producing a modified EVOH containing 0.3 to 40 mol % of the following structural unit (I) by melt-kneading EVOH and a monofunctional epoxy compound having a molecular weight of 500 or less in an extruder in the presence of a catalyst containing an ion of a metal belonging to Groups 3 to 12 of the periodic table. The modified EVOH is said to have excellent barrier properties, transparency, stretchability, and flex resistance.
[0004] [ka]
[0005] In the examples of Patent Document 1, a catalyst solution is prepared by dissolving equimolar amounts of zinc acetylacetonate monohydrate and trifluoromethanesulfonic acid in 1,2-dimethoxyethane, and a mixture of this catalyst solution and a monofunctional epoxy compound is fed to an extruder, which shows that a larger amount of structural unit (I) can be introduced into EVOH than when no catalyst solution is added. It is also described that the use of trisodium ethylenediaminetetraacetate trihydrate as a catalyst deactivator can suppress deterioration of the thermal stability of the resulting modified EVOH. The modified EVOH thus obtained contained 120 to 150 ppm (1.9 to 2.3 μmol / g) of zinc ions as catalyst residues.
[0006] Patent Document 2 describes a resin composition containing modified EVOH containing 0.3 to 40 mol % of the structural unit (I) and other thermoplastic resins. It describes examples of resin compositions containing the modified EVOH and unmodified EVOH, and examples of resin compositions containing the modified EVOH and polyolefin. [Prior art documents] [Patent documents]
[0007] [Patent Document 1] WO 02 / 092643 A1 [Patent Document 2] WO 03 / 072653 A1 Summary of the Invention [Problem to be solved by the invention]
[0008] However, the modified EVOH described in Patent Document 1 is easily discolored, and when melt-kneaded for a long period of time, the torque fluctuates greatly, and there is a problem with melt stability. The present invention has been made to solve such problems, and has an object to provide a method for producing a modified EVOH that is excellent in barrier properties, stretchability, etc., and also excellent in melt stability. Another object of the present invention is to provide a method for producing a resin composition containing such a modified EVOH and another resin. Another object of the present invention is to provide a method for producing a mixed pellet containing pellets of such a modified EVOH and pellets of another resin. Another object of the present invention is to provide a resin composition containing such a modified EVOH. [Means for solving the problem]
[0009] The above-mentioned problem is solved by providing a method for producing a modified ethylene-vinyl alcohol copolymer (C), which comprises melt-kneading an ethylene-vinyl alcohol copolymer (A) and a monofunctional epoxy compound (B) having 2 to 8 carbon atoms in an extruder to cause them to react with each other using a catalyst solution (D) that is an acetone solution containing zinc ions (F) and sulfonate ions.
[0010] In the above-mentioned production method, it is preferable to introduce the ethylene-vinyl alcohol copolymer (A), the monofunctional epoxy compound (B), and the catalyst solution (D) into an extruder and melt-knead them in the extruder to react the ethylene-vinyl alcohol copolymer (A) with the monofunctional epoxy compound (B). At this time, it is preferable to add a mixture of the monofunctional epoxy compound (B) and the catalyst solution (D) to the molten ethylene-vinyl alcohol copolymer (A).
[0011] In the above-mentioned production method, it is also preferable to impregnate the ethylene-vinyl alcohol copolymer (A) with the catalyst solution (D), introduce the resulting mixture into an extruder, and melt-knead the mixture with the monofunctional epoxy compound (B) in the extruder, thereby reacting the ethylene-vinyl alcohol copolymer (A) with the monofunctional epoxy compound (B).
[0012] In the above-mentioned production method, the ethylene content of the ethylene-vinyl alcohol copolymer (A) is preferably 5 to 55 mol % and the saponification degree is preferably 90 mol % or more. It is also preferable to melt-knead 1 to 50 parts by mass of the monofunctional epoxy compound (B) with respect to 100 parts by mass of the ethylene-vinyl alcohol copolymer (A). It is also preferable to use 0.05 to 1.0 μmol / g of zinc ions (F) in terms of the number of moles relative to the mass of the ethylene-vinyl alcohol copolymer (A).
[0013] In a preferred embodiment, the ethylene-vinyl alcohol copolymer (A) and the monofunctional epoxy compound (B) are melt-kneaded, and then the catalyst deactivator (E) is added and further melt-kneaded. In this case, it is preferred that the catalyst deactivator (E) is a chelating agent. It is also preferred that the catalyst deactivator (E) is a metal salt. It is also preferred that the ratio (E / F) of the number of moles of the catalyst deactivator (E) to the number of moles of the zinc ions (F) contained in the catalyst solution (D) is 1.5 to 40. It is also preferred that the ethylene-vinyl alcohol copolymer (A) and the monofunctional epoxy compound (B) are melt-kneaded, and the catalyst deactivator (E) is added after removing the unreacted monofunctional epoxy compound (B).
[0014] The modified ethylene-vinyl alcohol copolymer (C) obtained in the above production method preferably contains 0.3 to 40 mol % of the structural unit (I) represented by the following formula (I).
[0015] [ka]
[0016] (In formula (I), R 1 , R 2 , R 3 and R 4 each independently represents a hydrogen atom, an aliphatic hydrocarbon group having 1 to 6 carbon atoms, an alicyclic hydrocarbon group having 3 to 6 carbon atoms, or a phenyl group, the aliphatic hydrocarbon group, the alicyclic hydrocarbon group, and the phenyl group each optionally having a hydroxyl group, an alkoxy group, a carboxyl group, or a halogen atom; R3 and R 4 may be bonded to
[0017] A preferred embodiment of the present invention is a method for producing a resin composition, which includes a step of melt-kneading the modified ethylene-vinyl alcohol copolymer (C) obtained by the above-mentioned production method with an unmodified ethylene-vinyl alcohol copolymer or a polyolefin. Also, a preferred embodiment of the present invention is a method for producing a mixed pellet, which includes a step of pelletizing the modified ethylene-vinyl alcohol copolymer (C) obtained by the above-mentioned production method, and a step of dry-blending the pellets of the modified ethylene-vinyl alcohol copolymer (C) obtained with pellets of an unmodified ethylene-vinyl alcohol copolymer or a polyolefin.
[0018] The above-mentioned problem can also be solved by providing a resin composition comprising a modified ethylene-vinyl alcohol copolymer (C) containing 2 to 40 mol % of a structural unit (I) represented by the following formula (I) and zinc ions (F), wherein the content of the zinc ions (F) is 0.05 to 1.0 μmol / g.
[0019] [ka]
[0020] (In formula (I), R 1 , R 2 , R 3 and R 4 each independently represents a hydrogen atom, an aliphatic hydrocarbon group having 1 to 6 carbon atoms, an alicyclic hydrocarbon group having 3 to 6 carbon atoms, or a phenyl group, the aliphatic hydrocarbon group, the alicyclic hydrocarbon group, and the phenyl group each optionally having a hydroxyl group, an alkoxy group, a carboxyl group, or a halogen atom; R 3 and R 4 may be bonded to
[0021] In this case, it is preferable that the resin composition further contains an alkali metal ion (G), and the molar ratio (G / F) of the alkali metal ion (G) to the zinc ion (F) is 5-80. Effect of the Invention
[0022] According to the method for producing modified EVOH of the present invention, modified EVOH having excellent barrier properties, stretchability, etc., as well as excellent melt stability can be produced. According to the method for producing a resin composition of the present invention, a resin composition containing modified EVOH and another resin can be produced. According to the method for producing mixed pellets of the present invention, mixed pellets containing pellets of modified EVOH and pellets of another resin can be produced. Furthermore, the resin composition of the present invention contains modified EVOH with a high degree of modification, but has a low content of catalyst residue. Therefore, it has excellent barrier properties, stretchability, etc., as well as excellent melt stability and is resistant to coloration. [Brief description of the drawings]
[0023] [Figure 1] FIG. 2 is a schematic diagram showing the configuration of an extruder used in the examples. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0024] The modified EVOH (C) produced by the method of the present invention is a reaction product of EVOH (A) and a monofunctional epoxy compound (B), and preferably contains the following structural unit (I).
[0025] [ka]
[0026] In formula (I), R 1 , R 2 , R 3 and R 4 each independently represents a hydrogen atom, an aliphatic hydrocarbon group having 1 to 6 carbon atoms, an alicyclic hydrocarbon group having 3 to 6 carbon atoms, or a phenyl group, the aliphatic hydrocarbon group, the alicyclic hydrocarbon group, and the phenyl group each optionally having a hydroxyl group, an alkoxy group, a carboxyl group, or a halogen atom; R 3 and R 4 may be bonded to
[0027] Examples of the aliphatic hydrocarbon group include an alkyl group and an alkenyl group. Examples of the alicyclic hydrocarbon group include a cycloalkyl group and a cycloalkenyl group.
[0028] In a more preferred embodiment, the R 1 and R 2 In a further preferred embodiment, both of R 1 and R 2 are both hydrogen atoms, 3 and R 4 Among these, one is an aliphatic hydrocarbon group having 1 to 6 carbon atoms, and the other is a hydrogen atom. Preferably, the aliphatic hydrocarbon group is an alkyl group or an alkenyl group. From the viewpoint of placing importance on the gas barrier property when the modified EVOH (C) is used as a barrier material, the R 3 and R 4 It is more preferable that one of these is a methyl group or an ethyl group, and the other is a hydrogen atom.
[0029] In addition, from the viewpoint of gas barrier properties when using modified EVOH (C) as a barrier material, 1 and R 2 are both hydrogen atoms, 3 and R 4 Of these, one is (CH2) i It is also preferable that the substituent is a substituent represented by OH (wherein i is an integer of 1 to 6) and the other is a hydrogen atom. When gas barrier properties as a barrier material are particularly important, the above-mentioned (CH2) i In the substituent represented by OH, i is preferably an integer of 1 to 4, more preferably 1 or 2, and even more preferably 1.
[0030] The amount of the structural unit (I) contained in the modified EVOH (C) is preferably 0.3 to 40 mol%. The lower limit of the amount of the structural unit (I) is more preferably 0.5 mol% or more, even more preferably 1 mol% or more, and particularly preferably 2 mol% or more. On the other hand, the upper limit of the amount of the structural unit (I) is more preferably 20 mol% or less, even more preferably 15 mol% or less, and particularly preferably 10 mol% or less. By containing the structural unit (I) in an amount within the above range, a modified EVOH (C) having gas barrier properties, transparency, stretchability, and flex resistance can be obtained.
[0031] The ethylene content of the modified EVOH (C) is preferably 5 to 55 mol%. From the viewpoint of obtaining good stretchability and bending resistance of the modified EVOH (C), the lower limit of the ethylene content of the modified EVOH (C) is more preferably 10 mol% or more, even more preferably 20 mol% or more, even more preferably 25 mol% or more, and particularly preferably 31 mol% or more. On the other hand, from the viewpoint of the gas barrier property of the modified EVOH (C) of the present invention, the upper limit of the ethylene content of the modified EVOH (C) is more preferably 50 mol% or less, even more preferably 45 mol% or less. When the ethylene content is less than 5 mol%, the melt moldability may deteriorate, and when it exceeds 55 mol%, the gas barrier property may be insufficient. The saponification degree of the modified EVOH (C) means the saponification degree of the EVOH (A) described later.
[0032] The monomer units other than the structural unit (I) and the ethylene unit constituting the modified EVOH (C) are mainly vinyl alcohol units. The vinyl alcohol units are usually vinyl alcohol units that have not reacted with the monofunctional epoxy compound (B) among the vinyl alcohol units contained in the raw material EVOH (A). Also, unsaponified vinyl acetate units that may be contained in EVOH (A) are usually contained as they are in the modified EVOH (C). The content of the vinyl alcohol units is preferably 40 to 80 mol%. From the viewpoint of obtaining good gas barrier properties for the modified EVOH (C) of the present invention, the lower limit of the content of the vinyl alcohol units in the modified EVOH (C) is more preferably 45 mol% or more, and even more preferably 50 mol% or more. On the other hand, from the viewpoint of obtaining good stretchability and bending resistance for the modified EVOH (C) of the present invention, the upper limit of the content of the vinyl alcohol units in the modified EVOH (C) is more preferably 75 mol% or less, and even more preferably 70 mol% or less.
[0033] The modified EVOH (C) is a random copolymer containing these monomer units. In addition, other monomer units may be contained within the range that does not impair the object of the present invention, but the content of other monomer units other than the structural unit (I), ethylene unit, vinyl alcohol unit and vinyl acetate unit is preferably 5 mol% or less, more preferably 3 mol% or less, even more preferably 2 mol% or less, and may be 1 mol% or less, and may not substantially contain other monomer units. Examples of other monomer units include those exemplified as copolymerizable monomers described in EVOH (A) described later.
[0034] The melt flow rate (MFR) of the modified EVOH (C) (190°C, under a load of 2160 g) is preferably 0.1 to 30 g / 10 min, more preferably 0.3 to 25 g / 10 min, and even more preferably 0.5 to 20 g / 10 min. However, for those having a melting point near or exceeding 190°C, the MFR is measured under a load of 2160 g at multiple temperatures equal to or higher than the melting point, and is plotted on a semi-logarithmic graph with the reciprocal of absolute temperature on the horizontal axis and the logarithm of MFR on the vertical axis, and expressed as a value extrapolated to 190°C.
[0035] The present invention relates to a method for producing the above-mentioned modified EVOH (C). The present invention is a method for producing a modified ethylene-vinyl alcohol copolymer (C), which comprises melt-kneading an ethylene-vinyl alcohol copolymer (A) and a monofunctional epoxy compound (B) having 2 to 8 carbon atoms in an extruder to cause them to react with each other using a catalyst solution (D) that is an acetone solution containing zinc ions (F) and sulfonate ions.
[0036] The EVOH (A) used in the present invention is preferably one obtained by saponifying an ethylene-vinyl ester copolymer. A representative vinyl ester used in the production of EVOH is vinyl acetate, but other fatty acid vinyl esters (vinyl propionate, vinyl pivalate, etc.) can also be used. In addition to ethylene and vinyl esters, monomers that can be copolymerized with these, such as alkenes such as propylene, butylene, pentene, and hexene; 3-acyloxy-1-propene, 3-acyloxy-1-butene, 4-acyloxy-1-butene, 3,4-diacyloxy-1-butene, 3-acyloxy-4-methyl-1-butene, 4-acyloxy-2 ... 3-Acyloxy-3-methyl-1-butene, 3,4-diacyloxy-2-methyl-1-butene, 4-Acyloxy-1-pentene, 5-Acyloxy-1-pentene, 4,5-Diacyloxy-1-pentene, 4-Acyloxy-1-hexene, 5-Acyloxy-1-hexene, 6-Acyloxy-1-hexene, 5,6-Diacyloxy-1-hexene, 1,3-Diacetoxy-2-methyl It is also possible to copolymerize in the presence of a small amount of an alkene having an ester group such as olefin propane or a saponification product thereof; an unsaturated acid such as acrylic acid, methacrylic acid, crotonic acid, itaconic acid or an anhydride, salt, or mono- or dialkyl ester thereof; a nitrile such as acrylonitrile or methacrylonitrile; an amide such as acrylamide or methacrylamide; an olefin sulfonic acid such as vinyl sulfonic acid, allyl sulfonic acid, methallyl sulfonic acid or a salt thereof; a vinyl silane compound such as vinyl trimethoxy silane, vinyl triethoxy silane, vinyl tri (β-methoxy-ethoxy) silane, γ-methacryloxypropyl methoxy silane; an alkyl vinyl ether, vinyl ketone, N-vinyl pyrrolidone, vinyl chloride, vinylidene chloride, etc. In that case, the amount of copolymerization is usually 5 mol % or less, and it is preferable that it is substantially free of such an olefin sulfonic acid.
[0037] The ethylene content of the EVOH (A) used in the present invention is preferably 5 to 55 mol%. From the viewpoint of obtaining good stretchability and bending resistance of the modified EVOH (C), the lower limit of the ethylene content of the EVOH (A) is more preferably 10 mol% or more, even more preferably 20 mol% or more, particularly preferably 25 mol% or more, and even more preferably 31 mol% or more. On the other hand, from the viewpoint of the gas barrier property of the modified EVOH (C) of the present invention, the upper limit of the ethylene content of the EVOH (A) is more preferably 50 mol% or less, even more preferably 45 mol% or less. When the ethylene content is less than 5 mol%, the melt moldability may deteriorate, and when it exceeds 55 mol%, the gas barrier property may be insufficient. Here, when the EVOH (A) is composed of a blend of two or more types of EVOH having different ethylene contents, the average value calculated from the blending mass ratio is taken as the ethylene content.
[0038] The saponification degree of the vinyl ester component of the EVOH (A) used in the present invention is preferably 90 mol% or more. The saponification degree of the vinyl ester component is more preferably 95 mol% or more, further preferably 98 mol% or more, and optimally 99 mol% or more. If the saponification degree is less than 90 mol%, not only may the gas barrier property of the modified EVOH (C), particularly the gas barrier property at high humidity, decrease, but the thermal stability may become insufficient, and gels and particles may easily occur in the molded product. Here, when the EVOH (A) is composed of a blend of two or more kinds of EVOH with different saponification degrees, the average value calculated from the blending mass ratio is the saponification degree. The ethylene content and saponification degree of the EVOH (A) can be determined by a nuclear magnetic resonance (NMR) method.
[0039] Furthermore, EVOH blended with a boron compound can be used as EVOH (A) within the scope of the present invention. Here, examples of the boron compound include boric acids, boric acid esters, borate salts, boron hydrides, etc. Specifically, examples of the boric acids include orthoboric acid, metaboric acid, tetraboric acid, etc., examples of the borate esters include triethyl borate, trimethyl borate, etc., and examples of the borate salts include alkali metal salts, alkaline earth metal salts, borax, etc. of the above-mentioned various boric acids. Among these compounds, orthoboric acid (hereinafter, sometimes simply referred to as boric acid) is preferred.
[0040] When EVOH blended with a boron compound is used as EVOH (A), the content of the boron compound is preferably 20 to 2000 ppm, more preferably 50 to 1000 ppm, calculated as boron element. By blending the boron compound within this range, it is possible to obtain EVOH in which torque fluctuation during heat melting is suppressed. If the content is less than 20 ppm, such an effect is small, and if the content exceeds 2000 ppm, gelation is likely to occur, which may result in poor moldability.
[0041] In addition, EVOH (A) containing a phosphoric acid compound may be used as EVOH (A). This may stabilize the quality (coloring, etc.) of the resin. The phosphoric acid compound used in the present invention is not particularly limited, and various acids such as phosphoric acid and phosphorous acid and their salts can be used. The phosphate may be contained in any form of primary phosphate, secondary phosphate, or tertiary phosphate, but primary phosphate is preferred. The cation species is also not particularly limited, but an alkali metal salt is preferred. Among these, sodium dihydrogen phosphate and potassium dihydrogen phosphate are preferred. However, as described later, when EVOH (A) and a monofunctional epoxy compound (B) are reacted using a catalyst solution (D) containing zinc ions, the phosphate deactivates the catalyst, so the content is preferably low. Therefore, the content of the phosphoric acid compound in EVOH (A) is preferably 200 ppm or less, more preferably 100 ppm or less, and most preferably 50 ppm or less, calculated as a phosphoric acid radical. When a phosphoric acid compound is added, the preferred lower limit is 5 ppm or more.
[0042] As described later, in the method for producing the modified EVOH (C) of the present invention, the EVOH (A) and the monofunctional epoxy compound (B) are reacted by melt-kneading in an extruder using a catalyst solution (D), and the EVOH is exposed to heating conditions. If the EVOH (A) contains an excess of alkali metal salt and / or alkaline earth metal salt at this time, the catalyst is deactivated, so it is preferable to add them in small amounts. Therefore, it is preferable that the alkali metal salt contained in the EVOH (A) is 50 ppm or less in terms of metal element. In a more preferred embodiment, the alkali metal salt contained in the EVOH (A) is 30 ppm or less in terms of metal element, and more preferably 20 ppm or less. From the same viewpoint, it is preferable that the alkali earth metal salt contained in the EVOH (A) is 20 ppm or less in terms of metal element, and more preferably 10 ppm or less.
[0043] The intrinsic viscosity of the EVOH (A) used in the present invention is preferably 0.06 L / g or more. The intrinsic viscosity of the EVOH (A) is more preferably in the range of 0.07 to 0.2 L / g, further preferably 0.075 to 0.15 L / g, and particularly preferably 0.080 to 0.12 L / g. When the intrinsic viscosity of the EVOH (A) is less than 0.06 L / g, the stretchability and flex resistance may decrease. When the intrinsic viscosity of the EVOH (A) is more than 0.2 L / g, gels and bumps may easily occur in the molded product made of the modified EVOH (C).
[0044] The melt flow rate (MFR) (190°C, under a load of 2160g) of the EVOH (A) used in the present invention is preferably 0.1 to 30g / 10min, more preferably 0.3 to 25g / 10min, and even more preferably 0.5 to 20g / 10min. However, for EVOH (A) having a melting point near or exceeding 190°C, the melting point is measured under a load of 2160g at multiple temperatures equal to or higher than the melting point, and the MFR is plotted on a semi-logarithmic graph with the reciprocal of the absolute temperature on the horizontal axis and the logarithm of the MFR on the vertical axis, and the value is expressed by extrapolating to 190°C. Two or more EVOHs having different MFRs may be mixed and used.
[0045] The monofunctional epoxy compound (B) used in the present invention must be a monofunctional epoxy compound. That is, it must be an epoxy compound having only one epoxy group in the molecule. When a divalent or higher polyfunctional epoxy compound is used, the effect of the present invention cannot be achieved. However, in the manufacturing process of the monofunctional epoxy compound, a very small amount of a polyfunctional epoxy compound may be contained. As long as the effect of the present invention is not hindered, a monofunctional epoxy compound containing a very small amount of a polyfunctional epoxy compound can also be used as the monofunctional epoxy compound (B) in the present invention.
[0046] The number of carbon atoms in the monofunctional epoxy compound (B) used in the present invention is 2 to 8. Specifically, the compounds represented by the following formulae (II) to (IV) are preferably used.
[0047] [ka]
[0048] [ka]
[0049] [ka]
[0050] In the formula, R 5 R represents a hydrogen atom, an alkyl group having 1 to 6 carbon atoms, a cycloalkyl group having 3 to 6 carbon atoms, or a phenyl group. 6 and R 7 represents a hydrogen atom, an alkyl group having 1 to 5 carbon atoms, or a cycloalkyl group having 3 to 5 carbon atoms. Also, i represents an integer of 1 to 6.
[0051] The carbon number of the monofunctional epoxy compound is preferably 2 to 6, and more preferably 2 to 4. From the viewpoint of the gas barrier property of the obtained modified EVOH (C), the monofunctional epoxy compound is more preferably epoxyethane, epoxypropane, 1,2-epoxybutane, and glycidol, and more preferably epoxypropane and 1,2-epoxybutane.
[0052] The EVOH (A) is reacted with the monofunctional epoxy compound (B) to obtain a modified EVOH (C). The preferred mixing ratio of the EVOH (A) and the monofunctional epoxy compound (B) is 1 to 50 parts by mass of (B) per 100 parts by mass of (A), more preferably 2 to 40 parts by mass of (B) per 100 parts by mass of (A), and particularly preferably 5 to 35 parts by mass of (B) per 100 parts by mass of (A).
[0053] The catalyst solution (D) used in the reaction of EVOH (A) with the monofunctional epoxy compound (B) is an acetone solution containing zinc ions (F) and sulfonate ions. By melt-kneading using such a catalyst solution, the reaction of EVOH (A) with the monofunctional epoxy compound (B) can be efficiently carried out.
[0054] The catalyst solution (D) used in the present invention contains zinc ions (F). The most important thing about the metal ions used in the catalyst solution (D) is that they have a suitable Lewis acidity, and from this point of view, zinc ions (F) are used. By using zinc ions (F), the catalyst activity is high and the resulting modified EVOH (C) has excellent thermal stability.
[0055] The amount of zinc ions (F) added is preferably 0.05 to 1.0 μmol / g in terms of the number of moles of zinc ions (F) relative to the mass of EVOH (A). If the amount of zinc ions (F) is too much, when the resulting modified EVOH (C) is melt-kneaded for a long period of time, torque fluctuation is large, resulting in a problem in melt stability. In addition, the resulting modified EVOH (C) may be colored. The number of moles of zinc ions (F) is more preferably 0.9 μmol / g or less. On the other hand, if the amount of zinc ions (F) is too little, the effect of adding the catalyst (D) may not be fully exerted, and the number of moles is more preferably 0.1 μmol / g or more, even more preferably 0.2 μmol / g or more, and even more preferably 0.35 μmol / g or more.
[0056] The catalyst solution (D) contains sulfonate ions in addition to zinc ions (F). The sulfonate ions act as counter ions for the zinc ions (F), improving the Lewis acidity of the zinc ions (F) and improving the catalytic activity. The sulfonate ions do not react with the hydroxyl groups or epoxy groups of EVOH, and are thermally stable as an anion species itself. Examples of sulfonate ions include methanesulfonate ions, ethanesulfonate ions, trifluoromethanesulfonate ions, benzenesulfonate ions, and toluenesulfonate ions, with the trifluoromethanesulfonate ions being the most suitable.
[0057] In the examples of Patent Document 1, a catalyst solution in which equimolar amounts of zinc acetylacetonate monohydrate and trifluoromethanesulfonic acid are dissolved in 1,2-dimethoxyethane is used. That is, the number of moles of sulfonate ions contained in the catalyst solution is 1 time the number of moles of zinc ions (F). In contrast, in the present invention, the number of moles of sulfonate ions contained in the catalyst solution (D) is preferably 1.2 to 4 times the number of moles of zinc ions (F). By containing more sulfonate ions as counter ions of zinc ions (F), the Lewis acidity of zinc ions (F) is improved, and the reaction can proceed smoothly with a smaller amount of catalyst. The number of moles of sulfonate ions relative to the number of moles of zinc ions (F) is more preferably 1.5 times or more, and even more preferably 1.8 times or more. Also, it is more preferably 3 times or less, and even more preferably 2.5 times or less. It is optimal that the number of moles is substantially 2 times, and at this time, divalent zinc ions and monovalent sulfonate ions can form a salt without excess or deficiency. Since neither the zinc ions (F) nor the sulfonate ions volatilize, the ratio of the two is maintained at the same value even in the modified EVOH composition.
[0058] In the catalyst solution (D), the solvent that dissolves the zinc ions (F) and sulfonate ions is acetone. Patent Document 1 states that it is preferable to use an ether-based solvent, and describes an example in which a catalyst solution in which zinc acetylacetonate monohydrate and trifluoromethanesulfonic acid are dissolved in 1,2-dimethoxyethane is used. However, when 1,2-dimethoxyethane is used as the solvent, the resulting modified EVOH (C) is easily colored, and when the modified EVOH (C) is melt-kneaded for a long period of time, torque fluctuation is large, and there is a problem with melt stability. In addition, the ignition point of 1,2-dimethoxyethane is 202°C, which is close to the melt-kneading temperature, and there is a risk during production. In contrast, by using acetone as the solvent, the reaction can be advanced with a smaller amount of catalyst, and the amount of zinc ions (F) contained in the resulting modified EVOH (C) can be reduced. This can improve the problems of coloration and melt stability. Furthermore, the ignition point of acetone is 540°C, and the risk during production is also greatly reduced. The catalyst solution (D) may contain a small amount of a solvent other than acetone. Such a solvent may be any solvent that can be dissolved in acetone and does not inhibit the present invention, and an example of such a solvent is methanol. The content of the solvent is usually 20% by mass or less, preferably 10% by mass or less, and more preferably 5% by mass or less.
[0059] In the method for producing the modified EVOH (C) of the present invention, the EVOH (A) and the monofunctional epoxy compound (B) are reacted by melt-kneading them in an extruder using a catalyst solution (D) that is an acetone solution containing zinc ions (F) and sulfonate ions. The following two methods are exemplified as the method.
[0060] In the first method, EVOH (A), a monofunctional epoxy compound (B), and a catalyst solution (D) are introduced into an extruder and melt-kneaded in the extruder to react EVOH (A) with the monofunctional epoxy compound (B) to obtain a modified EVOH (C). In this case, it is preferable to add a mixture of the monofunctional epoxy compound (B) and the catalyst solution (D) to the molten EVOH (A).
[0061] The second method is a method in which EVOH (A) is impregnated with a catalyst solution (D), then introduced into an extruder, and melt-kneaded with a monofunctional epoxy compound (B) in the extruder to react EVOH (A) with the monofunctional epoxy compound (B) to obtain a modified EVOH (C). As a method for impregnating EVOH (A) with a catalyst solution (D), a method in which pellets of EVOH (A) are contacted with the catalyst solution (D) and then dried is mentioned as a suitable example. In this case, the dried pellets thus obtained are introduced into the extruder.
[0062] There is no particular limitation on the extruder used when reacting EVOH (A) with the monofunctional epoxy compound (B) in the extruder, but it is preferable to use a single screw extruder, a twin screw extruder, or a multi-screw extruder having two or more screws, and to react EVOH (A) with the monofunctional epoxy compound (B) at a temperature in the extruder of 180 to 250° C. If the temperature in the extruder exceeds 250° C., EVOH may deteriorate, and therefore the temperature is more preferably 230° C. or lower. On the other hand, if the temperature is less than 180° C., the reaction between EVOH (A) and the monofunctional epoxy compound (B) may not proceed sufficiently, and therefore the temperature is more preferably 190° C. or higher.
[0063] When a twin-screw extruder or a multi-screw extruder with two or more screws is used, it is easy to increase the pressure in the reaction zone by changing the screw configuration, and the reaction between EVOH (A) and the monofunctional epoxy compound (B) can be carried out efficiently. In the case of a single-screw extruder, it is possible to increase the pressure in the reaction zone by connecting two or more extruders and arranging a valve in the resin flow path between them. Similarly, two or more twin-screw extruders or two or more multi-screw extruders may be connected to produce the polymer.
[0064] Since the monofunctional epoxy compound (B) used in the present invention has a low boiling point in many cases, when the reaction system is heated in the production method by solution reaction, the monofunctional epoxy compound (B) may volatilize out of the system. However, by reacting EVOH (A) with the monofunctional epoxy compound (B) in the extruder, it is possible to suppress the volatilization of the monofunctional epoxy compound (B) out of the system. In particular, when the monofunctional epoxy compound (B) is added to the extruder, it is possible to increase the reactivity between EVOH (A) and the monofunctional epoxy compound (B) and to significantly suppress the volatilization of the monofunctional epoxy compound (B) out of the system by injecting it under pressure.
[0065] The method of mixing EVOH (A) and the monofunctional epoxy compound (B) during the reaction in the extruder is not particularly limited, and suitable examples include a method of spraying the monofunctional epoxy compound (B) on EVOH (A) before feeding it to the extruder, and a method of feeding EVOH (A) to the extruder and contacting it with the monofunctional epoxy compound (B) in the extruder. Among these, from the viewpoint of suppressing the volatilization of the monofunctional epoxy compound (B) to the outside of the system, a method of feeding EVOH (A) to the extruder and then adding the monofunctional epoxy compound (B) to EVOH (A) in the extruder is preferred. The position of addition of the monofunctional epoxy compound (B) to the extruder is also arbitrary, but from the viewpoint of the reactivity between EVOH (A) and the monofunctional epoxy compound (B), it is preferred to add the monofunctional epoxy compound (B) to EVOH (A) in a molten state.
[0066] In the step of adding the monofunctional epoxy compound (B), it is preferable to inject the monofunctional epoxy compound (B) under pressure. In this case, if the pressure is insufficient, problems such as a decrease in reaction rate and fluctuation in discharge amount occur. The required pressure varies greatly depending on the boiling point and extrusion temperature of the monofunctional epoxy compound (B), but is usually preferably in the range of 0.5 to 30 MPa, more preferably in the range of 1 to 20 MPa. The same applies when adding a mixture of the monofunctional epoxy compound (B) and the catalyst solution (D).
[0067] The position where the catalyst solution (D) is introduced into the extruder is not particularly limited, but it is preferable to add it at a place where the EVOH (A) is completely melted, since it can be mixed uniformly. It is preferable to add it at the same place where the monofunctional epoxy compound (B) is added or in the vicinity thereof. By mixing the catalyst solution (D) and the monofunctional epoxy compound (B) almost simultaneously, it is possible to minimize the deterioration of the EVOH (A) due to the influence of zinc ions (F), which are Lewis acids, and to ensure sufficient reaction time. Therefore, it is optimal to prepare a mixture of the catalyst solution (D) and the monofunctional epoxy compound (B) in advance and add it to the extruder from one place.
[0068] It is preferable to remove unreacted monofunctional epoxy compound (B) by a vent or the like downstream of the position where the monofunctional epoxy compound (B) is introduced into the extruder.
[0069] As described above, EVOH (A) and the monofunctional epoxy compound (B) are melt-kneaded in an extruder in the presence of zinc ions (F) as a catalyst, but it is preferable to add a catalyst deactivator (E) after melt-kneading EVOH (A) and the monofunctional epoxy compound (B) and further melt-knead them. If the catalyst is not deactivated, the thermal stability of the resulting modified EVOH (C) may be deteriorated, which may cause problems in use depending on the application.
[0070] The catalyst deactivator (E) used may be any one that reduces the Lewis acid activity of the zinc ion (F) that acts as a catalyst, and the type is not particularly limited. Metal salts such as alkali metal salts are preferably used. In order to deactivate a catalyst containing an anion of sulfonic acid, which is a strong acid, it is necessary to use an alkali metal salt of an anion of an acid weaker than sulfonic acid. This is because the counter ion of the zinc ion (F) that constitutes the catalyst is exchanged for an anion of a weak acid, and as a result, the Lewis acidity of the zinc ion (F) is reduced. The cation species of the alkali metal salt used in the catalyst deactivator (E) is not particularly limited, and sodium salts, potassium salts, and lithium salts are preferred examples. The anion species is also not particularly limited, and carboxylates, phosphates, and phosphonates are preferred examples.
[0071] The thermal stability is improved considerably even when salts such as sodium acetate and dipotassium hydrogen phosphate are used as the catalyst deactivator (E), but depending on the application, the improvement may still be insufficient. This is thought to be because zinc ions (F) still retain some Lewis acid activity, which acts as a catalyst for the decomposition and gelation of modified EVOH (C). As a method for further improving this point, it is preferable to add a chelating agent that strongly coordinates to zinc ions (F). Such a chelating agent can strongly coordinate to the ions of the metal, and as a result, the Lewis acidity can be almost completely lost, resulting in a modified EVOH (C) with excellent thermal stability. In addition, since the chelating agent is an alkali metal salt, it can also neutralize the sulfonic acid contained in the catalyst as described above.
[0072] Suitable examples of the chelating agent used as the catalyst deactivator (E) include oxycarboxylates, aminocarboxylates, and aminophosphonates. Specifically, examples of oxycarboxylates include disodium citrate, disodium tartrate, and disodium malate. Examples of aminocarboxylates include trisodium nitrilotriacetate, disodium ethylenediaminetetraacetate, trisodium ethylenediaminetetraacetate, tripotassium ethylenediaminetetraacetate, trisodium diethylenetriaminepentaacetate, trisodium 1,2-cyclohexanediaminetetraacetate, monosodium ethylenediaminediacetate, and monosodium N-(hydroxyethyl)iminodiacetate. Examples of aminophosphonates include hexasodium nitrilotrismethylenephosphonate and octasodium ethylenediaminetetra(methylenephosphonate). Among these, polyaminopolycarboxylic acids are suitable, and alkali metal salts of ethylenediaminetetraacetate are optimal in terms of performance and cost.
[0073] On the other hand, it has been found that a chelating agent such as an alkali metal salt of ethylenediaminetetraacetic acid may corrode metals constituting kneading equipment. This time, it has been found that the reaction between EVOH (A) and the monofunctional epoxy compound (B) can proceed smoothly even if the amount of zinc ions (F) used as a catalyst is reduced. Therefore, from the viewpoint of preventing corrosion of the kneading equipment, it is preferable to use an alkali metal salt of a monocarboxylic acid as a catalyst deactivator (E). The number of carbon atoms of the monocarboxylic acid is preferably 2 to 18, more preferably 6 or less, and even more preferably 4 or less. Specifically, acetic acid, propionic acid, and lactic acid are exemplified as preferred ones. The alkali metal is preferably sodium or potassium.
[0074] The amount of catalyst deactivator (E) added is not particularly limited, but it is preferable that the ratio (E / F) of the number of moles of catalyst deactivator (E) to the number of moles of zinc ions (F) is 1.5 to 40. If the ratio (E / F) is less than 1.5, the zinc ions (F) may not be sufficiently deactivated, and when melt-kneading is performed for a long period of time, torque fluctuation may be large and there may be a problem with melt stability. The ratio (E / F) is more preferably 2 or more, and even more preferably 2.5 or more. On the other hand, if the ratio (E / F) exceeds 40, the obtained modified EVOH (C) may be colored and the production cost may increase, so the ratio is more preferably 30 or less, and even more preferably 20 or less.
[0075] The method of introducing the catalyst deactivator (E) into the extruder is not particularly limited, but in order to disperse it uniformly, it is preferable to introduce the catalyst deactivator (E) as a solution to the molten modified EVOH (C) in order to disperse it uniformly. Considering the solubility of the catalyst deactivator (E) and the impact on the surrounding environment, it is preferable to add it as an aqueous solution.
[0076] The catalyst deactivator (E) may be added to the extruder after EVOH (A) and the monofunctional epoxy compound (B) are melt-kneaded in the presence of zinc ions (F). However, it is preferable to add the catalyst deactivator (E) after melt-kneading EVOH (A) and the monofunctional epoxy compound (B) in the presence of zinc ions (F) and removing the unreacted monofunctional epoxy compound (B). As described above, when the catalyst deactivator (E) is added as an aqueous solution, if the catalyst deactivator (E) is added before removing the unreacted monofunctional epoxy compound (B), water will be mixed into the monofunctional epoxy compound (B) that is removed and recovered by venting or the like, and the separation operation will be troublesome. It is also preferable to remove water by venting or the like after adding the aqueous solution of the catalyst deactivator (E).
[0077] In the production process of the present invention, a suitable production process when using a catalyst deactivator (E) is as follows: (1) Melting process of EVOH (A); (2) adding a mixture of a monofunctional epoxy compound (B) and a catalyst solution (D); (3) a step of removing the unreacted monofunctional epoxy compound (B); (4) adding an aqueous solution of a catalyst deactivator (E); (5) Water removal process under reduced pressure; An example is one consisting of the steps of:
[0078] The resin composition obtained by the production method of the present invention as described above preferably contains modified EVOH (C) containing 0.3 to 40 mol % of the structural unit (I) represented by the above formula (I) and zinc ions (F), and more preferably the content of zinc ions (F) is 0.05 to 1.0 μmol / g. Here, the zinc ions (F) in the modified EVOH composition are contained as catalyst residues when the catalyst solution (D) is used in the above production method.
[0079] The content of zinc ions (F) in the modified EVOH composition of the present invention is more preferably 0.05 to 1.0 μmol / g. By having the content of zinc ions (F) of 1.0 μmol / g or less, even when melt-kneaded for a long period of time, the resin composition has small torque fluctuation and excellent melt stability. The content of zinc ions (F) is more preferably 0.9 μmol / g or less. On the other hand, by having the content of zinc ions (F) of 0.05 μmol / g or more, the reaction between EVOH (A) and the monofunctional epoxy compound (B) is promoted. The content of zinc ions (F) is more preferably 0.1 μmol / g or more, even more preferably 0.2 μmol / g or more, and particularly preferably 0.35 μmol / g or more.
[0080] In addition, the modified EVOH composition of the present invention preferably contains an alkali metal ion (G), and the molar ratio (G / F) of the alkali metal ion (G) to the zinc ion (F) is 5 to 80. Here, the alkali metal ion is mainly contained as a residue when the catalyst deactivator (E) is used in the above-mentioned production method. The alkali metal ion (G) is preferably a sodium ion and / or a potassium ion. By having a molar ratio (G / F) of 5 or more, the catalyst can be effectively deactivated, and even when melt-kneaded for a long period of time, the resin composition has small torque fluctuation and excellent melt stability. The molar ratio (G / F) is more preferably 6 or more. On the other hand, if the molar ratio (G / F) exceeds 80, the resin composition may turn yellow. The molar ratio (G / F) is more preferably 60 or less, and even more preferably 40 or less.
[0081] At least one selected from the group consisting of alkali metal salts, alkaline earth metal salts, carboxylic acids, and phosphoric acid compounds can also be added to the modified EVOH composition of the present invention after the modified EVOH (C) is obtained by the reaction of EVOH (A) with the epoxy compound (B). In general, in order to improve various physical properties of EVOH, such as improving adhesion and suppressing coloration, at least one selected from the group consisting of alkali metal salts, alkaline earth metal salts, carboxylic acids, and phosphoric acid compounds is often added to EVOH as necessary. However, as described above, the addition of the various compounds shown above may cause coloration, viscosity reduction, and the like during the reaction of EVOH (A) with the epoxy compound (B) in an extruder. For this reason, it is preferable to remove the remaining epoxy compound (B) through a vent after the reaction of EVOH (A) with the epoxy compound (B), and then add at least one selected from the group consisting of alkali metal salts, alkaline earth metal salts, carboxylic acids, and phosphoric acid compounds to the obtained modified EVOH (C). By adopting this addition method, the modified EVOH composition of the present invention can be obtained without problems such as coloration and viscosity reduction.
[0082] The modified EVOH composition of the present invention may also contain various additives as necessary. Examples of such additives include antioxidants, plasticizers, heat stabilizers, UV absorbers, antistatic agents, lubricants, colorants, fillers, and other polymer compounds, and these may be blended within a range that does not impair the effects of the present invention. The total content of polymer compounds other than the modified EVOH (C) and various additives may be 10% by mass or less, 5% by mass or less, or 1% by mass or less.
[0083] The modified EVOH composition of the present invention has an oxygen transmission rate of 100 cc·20 μm / m at 20°C and 65% RH. 2 The upper limit of the oxygen permeability is 50cc·20μm / m 2 ·day·atm or less is more preferable, and 20cc·20μm / m 2 It is more preferable that the concentration is 10cc·day·atm or less, and 10cc·20μm / m 2 Since the modified EVOH composition of the present invention is a resin having such a low oxygen transmission rate, it is preferably used as a barrier material, and is particularly preferably used as a container for packaging food.
[0084] The modified EVOH composition of the present invention is preferably formed into various molded products such as films, sheets, containers, pipes, hoses, fibers, etc., by melt molding. These molded products can be pulverized and molded again for reuse. Films, sheets, fibers, etc. can also be uniaxially or biaxially stretched. Possible melt molding methods include extrusion molding, melt spinning, injection molding, injection blow molding, etc. The melting temperature varies depending on the melting point of the modified EVOH (C), etc., but is preferably about 120 to 270°C.
[0085] The modified EVOH composition of the present invention is preferably used as an extrusion molded product. The manufacturing method of the extrusion molded product is not particularly limited, but suitable examples include film extrusion cast molding, sheet extrusion cast molding, pipe extrusion molding, hose extrusion molding, profile extrusion molding, extrusion blow molding, inflation extrusion molding, etc. In addition, the extrusion molded product obtained by these molding methods can be subjected to secondary processing such as uniaxial or biaxial stretching, or thermoforming.
[0086] The modified EVOH composition of the present invention can also be used as a monolayer molded product. From the viewpoint of effectively utilizing the modified EVOH composition of the present invention, which has excellent barrier properties, impact resistance, and bending resistance, preferred monolayer molded products made of the modified EVOH composition include films, extrusion blow molded products (preferably bottles, etc.), flexible packaging containers (preferably flexible tubes or flexible pouches, etc.), pipes, hoses, and profile molded products. As the film, from the viewpoint of making the most of the property of the modified EVOH composition of the present invention, namely, excellent stretchability, a stretched film is particularly preferred. Of these, a stretched film that is stretched at least 2 times in at least one axial direction is preferred. Furthermore, it is also preferred to use the stretched film as a heat shrinkable film.
[0087] As described above, the modified EVOH composition of the present invention can be used as a single-layer molded product, but it is also preferable to use it as a multi-layer structure containing at least one layer made of the modified EVOH composition. The layer structure of the multi-layer structure may be Barrier / R, R / Barrier / R, Barrier / Ad / R, Reg / Barrier / R, R / Ad / Barrier / Ad / R, R / Reg / Ad / Barrier / Ad / Reg / R, etc., where Barrier is the modified EVOH composition of the present invention, which is often used as a barrier material, Ad is an adhesive resin, R is a resin other than the barrier material, and Reg is a scrap recovery layer. However, the layer structure is not limited thereto. In addition, when resins other than the modified EVOH composition are provided on both sides of the layer made of the modified EVOH composition, the resins may be different or the same. Furthermore, the recovered resin may be blended with a resin other than the modified EVOH composition. Each layer may be a single layer, or in some cases, may be multi-layered.
[0088] A resin composition containing a modified EVOH (C) containing 0.3 to 40 mol % of the structural unit (I) represented by the formula (I) and an unmodified EVOH or a polyolefin, and containing 0.05 to 1.0 μmol / g of zinc ions (F) relative to the mass of the modified EVOH (C), is also a preferred embodiment of the present invention. This resin composition can be produced by melt-kneading the modified EVOH (C) and the unmodified EVOH or a polyolefin. In this specification, the term "unmodified EVOH" refers to an EVOH that does not contain the structural unit (I).
[0089] The blending ratio of the modified EVOH (C) and the unmodified EVOH or polyolefin is not particularly limited, but preferably contains 1 to 99 mass % of the modified EVOH (C) and 1 to 99 mass % of the unmodified EVOH or polyolefin.
[0090] By preparing a resin composition containing modified EVOH (C) and unmodified EVOH, it is possible to greatly improve secondary processability, fatigue resistance, stretchability, or interlayer adhesion without significantly decreasing the barrier properties and transparency of the unmodified EVOH. The unmodified EVOH used here can be the same as the above-mentioned EVOH (A) used as a raw material for modified EVOH (C), but it is appropriately selected depending on the composition of the modified EVOH (C) to be blended and the application of the resin composition.
[0091] It is preferable that the resin composition is composed of 1 to 50% by mass of modified EVOH (C) and 50 to 99% by mass of unmodified EVOH. That is, it is preferable that unmodified EVOH is a main component and modified EVOH (C) is a secondary component. By doing so, flexibility and secondary processability can be imparted to the resin composition without significantly impairing the gas barrier property and transparency inherent to unmodified EVOH. In addition, since the production cost of modified EVOH (C) is higher than that of unmodified EVOH, it is economically advantageous. The content of modified EVOH (C) is more preferably 5% by mass or more, and even more preferably 10% by mass or more. In this case, the content of unmodified EVOH is more preferably 95% by mass or less, and even more preferably 90% by mass or less. On the other hand, the content of modified EVOH (C) is more preferably 40% by mass or less, and even more preferably 30% by mass or less. In this case, the content of unmodified EVOH is more preferably 60% by mass or more, and even more preferably 70% by mass or more.
[0092] It is also preferable to use a resin composition containing modified EVOH (C) and polyolefin. Polyolefin is highly useful because it has excellent mechanical properties and processability and is low in cost, but has low barrier properties. By blending modified EVOH (C) with this, the barrier properties can be improved without significantly impairing impact resistance, fatigue resistance, processability, etc. The polyolefin used here is not particularly limited. For example, polypropylene, polyethylene, ethylene-propylene copolymer, and ethylene-vinyl acetate copolymer are preferably used, and polyethylene and polypropylene are particularly preferably used.
[0093] The resin composition preferably comprises 10-60% by mass of modified EVOH (C) and 40-90% by mass of polyolefin. That is, the resin composition preferably contains about half or more of polyolefin. This is because the resin composition can be imparted with barrier properties without significantly impairing the mechanical properties and processability inherent to polyolefin. In addition, since the production cost of modified EVOH (C) is significantly higher than that of polyolefin, this is an economically advantageous blending ratio. The content of modified EVOH (C) is more preferably 20% by mass or more, and the content of polyolefin is 80% by mass or less. On the other hand, the content of modified EVOH (C) is more preferably 50% by mass or less, and the content of polyolefin is even more preferably 50% by mass or more.
[0094] A mixed pellet containing pellets of the modified EVOH composition and pellets of unmodified EVOH or polyolefin is also a preferred embodiment. The mixed pellets can be produced by a production method including a step of pelletizing the modified EVOH (C) obtained by the production method of the present invention, and a step of dry-blending the modified EVOH (C) pellets obtained with pellets of unmodified EVOH or polyolefin. With such mixed pellets, a molded product of the resin composition can be easily obtained by simply introducing the pellets into a kneading device and melt-molding them.
[0095] The resin composition obtained by the production method of the present invention and its uses have been described above. Among the resin compositions obtained in this way, there is a new resin composition that contains a highly modified EVOH but has a low content of catalyst residue. That is, another aspect of the present invention is a resin composition that contains a modified ethylene-vinyl alcohol copolymer (C) containing 2 to 40 mol % of a structural unit (I) represented by the following formula (I) and zinc ions (F), and the content of zinc ions (F) is 0.05 to 1.0 μmol / g.
[0096] [ka]
[0097] (In formula (I), R 1 , R 2 , R 3 and R 4 each independently represents a hydrogen atom, an aliphatic hydrocarbon group having 1 to 6 carbon atoms, an alicyclic hydrocarbon group having 3 to 6 carbon atoms, or a phenyl group, the aliphatic hydrocarbon group, the alicyclic hydrocarbon group, and the phenyl group each optionally having a hydroxyl group, an alkoxy group, a carboxyl group, or a halogen atom; R 3 and R 4 may be bonded to.
[0098] The method for producing this resin composition is not particularly limited, and the above description of the resin composition obtained by the production method of the present invention and its uses is also applicable, except that the content of the structural unit (I) is 2 mol % or more. EXAMPLES
[0099] The present invention will be described in detail below with reference to examples and comparative examples, but the present invention is not limited thereto. Analysis of EVOH (A) and modified EVOH (C) was carried out according to the following methods.
[0100] (1) Ethylene content and degree of saponification of EVOH (A) Deuterated dimethyl sulfoxide was used as the solvent. 1 The values were calculated from the spectrum obtained by H-NMR (nuclear magnetic resonance) measurement (using a JNM-GX-500 model manufactured by JEOL Ltd.).
[0101] (2) Intrinsic viscosity of EVOH (A) 0.20 g of dried pellets made of dried EVOH (A) as a sample was precisely weighed and dissolved in 40 ml of hydrous phenol (water / phenol = 15 / 85: mass ratio) at 60°C for 3 to 4 hours. The viscometer was used to measure the intrinsic viscosity [η] at 30°C (t0 = 90 seconds), and the intrinsic viscosity was calculated using the following formula. [η]=(2×(ηsp-lnηrel)) 1 / 2 / C (L / g) ηsp=t / t0-1 (specific viscosity) ηrel=t / t0 (relative viscosity) C:EVOH concentration (g / L) t0: The time when the blank (water-containing phenol) passes through the viscometer t: The time it takes for the aqueous phenol solution containing the sample to pass through the viscometer
[0102] (3) Determination of acetic acid content in EVOH(A) 20 g of dried pellets of EVOH (A) as a sample were placed in 100 ml of ion-exchanged water and extracted by heating at 95°C for 6 hours. The extract was neutralized and titrated with 1 / 50 N NaOH using phenolphthalein as an indicator to quantify the acetic acid content.
[0103] (4) Quantitative determination of Na ions, K ions, Mg ions and Ca ions in EVOH (A) and modified EVOH (C) 10 g of dried pellets of EVOH (A) or modified EVOH (C) as a sample was added to 50 ml of 0.01N hydrochloric acid solution and stirred at 95°C for 6 hours. The aqueous solution after stirring was quantitatively analyzed using ion chromatography to quantify the amounts of Na, K, Mg, and Ca ions. The column used was an ICS-C25 manufactured by Yokogawa Electric Corporation, and the eluent was an aqueous solution containing 5.0 mM tartaric acid and 1.0 mM 2,6-pyridinedicarboxylic acid. For the quantification, calibration curves prepared using aqueous sodium chloride, potassium chloride, magnesium chloride, and calcium chloride solutions were used.
[0104] (5) Determination of phosphate ions in EVOH (A) and modified EVOH (C) 10 g of dried pellets of EVOH (A) or modified EVOH (C) as a sample were added to 50 ml of 0.01N hydrochloric acid solution and stirred at 95°C for 6 hours. The aqueous solution after stirring was quantitatively analyzed using ion chromatography to determine the amount of phosphate ions. The column used was an ICS-A23 manufactured by Yokogawa Electric Corporation, and the eluent was an aqueous solution containing 2.5 mM sodium carbonate and 1.0 mM sodium bicarbonate. A calibration curve created with an aqueous solution of sodium dihydrogen phosphate was used for the quantification.
[0105] (6) Quantitative determination of zinc ions (F) in modified EVOH (C) 10 g of the modified EVOH(C) dried pellets as a sample were added to 50 ml of 0.01N hydrochloric acid solution and stirred at 95°C for 6 hours. The aqueous solution after stirring was analyzed by ICP emission spectrometry. PerkinElmer's Optima4300DV was used as the instrument. The measurement wavelength was 206.20 nm for measuring zinc ions. A calibration curve created using a commercially available zinc standard solution was used for quantification.
[0106] (7) Melting points of EVOH (A) and modified EVOH (C) The melting points of EVOH (A) and modified EVOH (C) were measured in accordance with JIS K7121 using a differential scanning calorimeter (DSC) RDC220 / SSC5200H manufactured by Seiko Instruments Inc. However, indium and lead were used for temperature calibration.
[0107] Example 1 100 parts by mass of hydrous pellets (moisture content: 130% (dry base): 57% (wet base)) made of an ethylene-vinyl alcohol copolymer having an ethylene content of 32 mol%, a saponification degree of 99.6 mol%, and an intrinsic viscosity of 0.0882 L / g were immersed and stirred in 370 parts by mass of an aqueous solution containing 0.1 g / L of acetic acid and 0.044 g / L of potassium dihydrogen phosphate at 25° C. for 6 hours. The obtained pellets were dried at 105° C. for 20 hours to obtain dried EVOH pellets. The dried EVOH pellets had a potassium content of 8 ppm (metal element equivalent), an acetic acid content of 53 ppm, a phosphoric acid compound content of 20 ppm (phosphate radical equivalent), and an alkaline earth metal salt (Mg salt or Ca salt) content of 0 ppm. The MFR of the dried pellets was 8 g / 10 min (190° C., under a load of 2160 g). The EVOH pellets thus obtained were used as EVOH (A). Epoxypropane was used as the monofunctional epoxy compound (B), and a solution containing 3.3 mass % of zinc trifluoromethanesulfonate, 0.6 mass % of methanol, and 96.0 mass % of acetone was used as the catalyst solution (D).
[0108] A TEM-35BS extruder (37 mmφ, L / D=52.5) manufactured by Toshiba Machine Co., Ltd. was used, and the screw configuration, vent, and pressure inlet were installed as shown in FIG. 1. Barrel C1 was water-cooled, barrels C2 to C15 were set to 200°C, and the screw rotation speed was 250 rpm. The above EVOH (A) pellets were added from the resin feed port of C1 at a rate of 11 kg / hr, the internal pressure of vent 1 was reduced to 60 mmHg, and epoxypropane was added from pressure inlet 1 of C8 at a rate of 1.5 kg / hr and the catalyst solution (D) was added at a rate of 0.07 kg / hr, and then the two were mixed and fed (pressure at the time of feeding: 3 MPa). Next, unreacted epoxypropane was removed from vent 2 at normal pressure, and then an 8.2 mass% aqueous solution of trisodium ethylenediaminetetraacetate trihydrate (EDTA) was added as a catalyst deactivator (E) from pressure inlet 2 of C13 at a rate of 0.11 kg / hr.
[0109] In the above melt-kneading operation, the mixing ratio of the monofunctional epoxy compound (B) was 13.6 parts by mass relative to 100 parts by mass of EVOH (A). 0.57 μmol / g of the catalyst solution (D) was added in terms of the number of moles of zinc ions (F) relative to the mass of EVOH (A). The ratio (E / F) of the number of moles of the catalyst deactivator (E) relative to the number of moles of zinc ions (F) contained in the catalyst solution (D) was 3.5.
[0110] The internal pressure of the vent 3 was reduced to 20 mmHg, and moisture was removed to obtain modified EVOH (C). The obtained modified EVOH (C) had an MFR of 7 g / 10 min (190° C., under a load of 2160 g) and a melting point of 132° C. The zinc ion content was 35 ppm (0.54 μmol / g), and the alkali metal ion (G) content was 138 ppm (5.9 μmol / g) in terms of metal elements [sodium: 130 ppm (5.7 μmol / g), potassium: 8 ppm (0.2 μmol / g)]. The alkaline earth metal salt (Mg salt or Ca salt) content was 0 ppm. The alkaline earth metal salt content was also 0 ppm in other examples and comparative examples of the present application. The molar ratio (G / F) of alkali metal ion (G) to zinc ion (F) was 10.9. The number of moles of the sulfonate ions contained was twice the number of moles of the zinc ions (F), and this was also the case in Examples 2 to 11.
[0111] The chemical structure of the modified EVOH (C) thus obtained, modified with epoxypropane, was determined by trifluoroacetylation of the modified EVOH (C) and then performing NMR measurement according to the procedure described in Patent Document 1. As a result, the ethylene content of the modified EVOH (C) was 32 mol %, and the content of the structural unit (I) was 5.5 mol %.
[0112] (a) Preparation of monolayer film The modified EVOH (C) thus obtained was used to produce a film using a film-forming machine consisting of a 40φ extruder (PLABOR GT-40-A manufactured by Plastics Engineering Research Institute) and a T-die under the following extrusion conditions to obtain a single-layer film having a thickness of 25 μm. Type: Single screw extruder (non-vent type) L / D: 24 Caliber: 40mmφ Screw: Single-row full-flight type, surface-nitrided steel Screw rotation speed: 40 rpm Die: 550mm wide coat hanger die Lip gap: 0.3mm Cylinder and die temperature settings: C1 / C2 / C3 / Adapter / Die =180 / 200 / 210 / 210 / 210(℃)
[0113] Using the monolayer film prepared as described above, the oxygen transmission rate and haze were measured and a bending resistance test was carried out according to the following methods (b) to (d).
[0114] (b) Measurement of oxygen transmission rate The monolayer film prepared above was conditioned at 20°C and 65% RH for 5 days. Two samples of the conditioned monolayer film were used to measure the oxygen transmission rate under conditions of 20°C and 65% RH using a MOCON OX-TRAN2 / 20 model manufactured by Modern Controls, in accordance with the method described in JIS K7126 (constant pressure method), and the average value was calculated. The oxygen transmission rate was 1.5cc 20μm / m 2 1 day atm, demonstrating good barrier properties.
[0115] (c) Haze measurement The haze of the monolayer film prepared above was measured in accordance with JIS D8741 using an integral HTR meter manufactured by Nippon Seimitsu Kogaku Co., Ltd. The haze was 0.1%, indicating very good transparency.
[0116] (d) Evaluation of bending resistance 50 sheets of the monolayer film prepared above were cut to 21 cm x 30 cm, and each film was conditioned at 20°C-65% RH for 5 days. After that, the film was bent 50 times, 75 times, 100 times, 125 times, 150 times, 175 times, 200 times, 225 times, 250 times, and 300 times according to ASTM F 392-74 using a Gelbo Flex Tester manufactured by Rigaku Kogyo Co., Ltd., and the number of pinholes was measured. At each number of times of bending, the measurement was performed 5 times, and the average value was taken as the number of pinholes. The number of times of bending (P) was taken on the horizontal axis and the number of pinholes (N) on the vertical axis, and the above measurement results were plotted, and the number of times of bending (Np1) when the number of pinholes was 1 was calculated by extrapolation and expressed as two significant digits. As a result, Np1 was 160 times, indicating extremely excellent bending resistance.
[0117] (e) Evaluation of stretchability Next, a multilayer sheet (ionomer resin layer / adhesive resin layer / modified EVOH (C) layer / adhesive resin layer / ionomer resin layer) was produced using the obtained modified EVOH (C) under the following coextrusion molding conditions using the following three-kind five-layer coextrusion device. The sheet was structured such that the outermost layers of ionomer resin (Mitsui DuPont Polychemical's "Himilan 1652") were each 250 μm thick, the adhesive resin (Mitsui Chemicals' "Admer NF500") layers were each 30 μm thick, and the modified EVOH (C) layer was 90 μm thick.
[0118] The coextrusion conditions were as follows: Layer composition: Ionomer resin / Adhesive resin / Modified EVOH(C) / Adhesive resin / Ionomer resin (Thickness 250 / 30 / 90 / 30 / 250: Unit is μm) Extrusion temperature for each resin: C1 / C2 / C3 / die=170 / 170 / 220 / 220℃ Extruder specifications for each resin: Ionomer resins; 32φ Extruder GT-32-A type (manufactured by Plastics Engineering Research Institute Co., Ltd.) adhesive resin; 25φ extruder P25-18AC (manufactured by Osaka Seiki Kogyo Co., Ltd.) Modified EVOH (C); 20φ Extruder Lab Machine ME Type CO-EXT (manufactured by Toyo Seiki Co., Ltd.) T-die specifications: 300mm width, 3 types, 5 layers (manufactured by Plastics Technology Research Institute Co., Ltd.) Cooling roll temperature: 50℃ Take-off speed: 4m / min
[0119] The resulting multilayer sheet was placed in a pantograph-type biaxial stretching device manufactured by Toyo Seiki Seisakusho, and subjected to simultaneous biaxial stretching at 60° C. and a stretch ratio of 4×4. The appearance of the film after stretching was evaluated according to the following criteria. Judgment criteria A: No unevenness or localized thickness deviation. B: There is slight unevenness, but no localized thickness deviation. C: There is slight unevenness and slight localized thickness deviation, but it is usable. D: There are large unevenness and large localized thickness deviations. E: The film was torn. The stretched film of this example had no unevenness or localized thickness deviation, and was rated an A.
[0120] (f) Evaluation of torque stability during long-term operation A melt-kneading test was carried out using the obtained modified EVOH (C) to evaluate the stability during long-term operation. A 60 g sample of modified EVOH (C) was melt-kneaded using a Labo Plastomill (Toyo Seiki Co., Ltd.: 4C150 type, R-60 type, biaxial counter-rotation) under a nitrogen atmosphere at 230 ° C. and 100 rpm, and the torque change was measured. The kneading time was 180 minutes, and the difference ΔT between the initial torque value T0 at the start of kneading and the minimum torque value Tmin during the kneading time was evaluated. The minimum value Tmin correlates with the degree of decomposition of the resin under high-temperature shear, and the smaller ΔT, the higher the long-term operational stability during melt molding of the resin. The ΔT of the modified EVOH (C) obtained in this example was 0.3 (kgf·m).
[0121] (g) Interlayer adhesion test The obtained modified EVOH (C), polyethylene resin ("Novatec LD LJ400" manufactured by Japan Polyethylene Co., Ltd.: low density polyethylene, melting point 108 ° C), and adhesive resin ("Admer NF518" manufactured by Mitsui Chemicals, Inc.: maleic anhydride graft modified linear low density polyethylene, melting point 120 ° C) were used to produce a 3-type 5-layer unstretched multilayer film (polyethylene / adhesive resin / modified EVOH (C) / adhesive resin / polyethylene = 144 μm / 18 μm / 18 μm / 18 μm / 144 μm). The thickness of the coextruded film was adjusted by appropriately changing the screw rotation speed and take-up roll speed. The extruder, extrusion conditions, and die used were as follows.
[0122] Modified EVOH (C): Extruder: Single-screw extruder (Toyo Seiki Co., Ltd. Lab machine ME type CO-EXT) Screw: Diameter 20mmφ, L / D20, full flight screw Extrusion temperature: feeding section / compression section / metering section / die = 175 / 200 / 220 / 220℃ ·Adhesive resin Extruder: Single screw extruder (Technobel Co., Ltd. SZW20GT-20MG-STD) Screw: Diameter 20mmφ, L / D20, full flight screw Extrusion temperature: feeding section / compression section / metering section / die = 175 / 200 / 220 / 220℃ Polyethylene resin Extruder: Single screw extruder (Plastic Engineering Research Institute Co., Ltd. GT-32-A) Screw: Diameter 32mmφ, L / D28, full flight screw Extrusion temperature: feeding section / compression section / metering section / die = 175 / 200 / 220 / 220℃ ·Thailand 300mm wide 3-type 5-layer coat hanger die (manufactured by Plastics Engineering Research Institute Co., Ltd.), die temperature 220℃
[0123] The multilayer structure obtained as above was conditioned at 23°C and 50% RH, and then a sample 150 mm long and 15 mm wide was cut along the extrusion direction, and peel strength was measured when peeled in a T-peel mode at a tensile speed of 250 mm / min under an atmosphere of 23°C and 50% RH using an autograph "DCS-50M tensile tester" manufactured by Shimadzu Corporation, and the evaluation was made according to the following criteria, resulting in an A rating. Note that the peel interface was the interface between the modified EVOH (C) layer and the adhesive resin layer. Judgment criteria A:250g / 15mm or more B: 100g / 15mm or more, less than 250g / 15mm C: Less than 100g / 15mm
[0124] (h) Yellowness of Resin Composition Pellets The yellowness index (YI) of the obtained resin composition pellets was measured using a spectrophotometer (HunterLab's "LabScan XE Sensor") and rated according to the following criteria, resulting in an evaluation of A. The YI value is an index representing the yellowness of an object, and a higher YI value indicates a stronger yellowness, whereas a lower YI value indicates a weaker yellowness and less coloring. Judgment criteria A: Less than 15 B: 15 to 25 C: 25 to 35 D: 35 to under 45 E: 45 and above
[0125] The manufacturing method of modified EVOH (C) is shown in Table 1, its composition in Table 2, and the evaluation results of the film and resin in Table 3.
[0126] Example 2 As the raw EVOH pellets, 5 kg of dried pellets of EVOH {acetic acid content 53 ppm, sodium content 1 ppm (metal element equivalent), potassium content 8 ppm (metal element equivalent), phosphoric acid compound content 20 ppm (phosphate radical equivalent)} with ethylene content 44 mol%, saponification degree 99.8 mol%, intrinsic viscosity 0.096 L / g, MFR = 5 g / 10 min (190 ° C, under 2160 g load) was placed in a polyethylene bag. Then, 395 g of the same catalyst solution (D) as in Example 1 was added to the EVOH in the bag. The EVOH to which the catalyst solution was added as described above was heated at 50 ° C for 10 hours with the bag closed while occasionally shaking and mixing, and the EVOH was impregnated with the catalyst solution (D). The obtained EVOH was vacuum dried at 30 ° C to obtain EVOH pellets containing zinc ions (F) and sulfonate ions.
[0127] As EVOH (A), a pellet mixture was used in which 90 parts by mass of the raw EVOH pellets were dry-blended with 10 parts by mass of the EVOH pellets containing zinc ions and sulfonate ions. 1,2-epoxybutane was used as the monofunctional epoxy compound (B).
[0128] A TEM-35BS extruder (37 mmφ, L / D=52.5) manufactured by Toshiba Machine Co., Ltd. was used, and the screw configuration, vent, and pressure inlet were installed as shown in FIG. 1. Barrel C1 was water-cooled, barrels C2 to C3 were set to 200°C, and barrels C4 to C15 were set to 220°C, and the screw rotation speed was 200 rpm. The pellet mixture was fed as EVOH (A) from the resin feed port of C1 at a rate of 11 kg / hr, the internal pressure of vent 1 was reduced to 60 mmHg, and epoxybutane was fed from pressure inlet 1 of C8 at a rate of 2.5 kg / hr (pressure at the time of feeding: 3.5 MPa). The internal pressure of vent 2 was reduced to 200 mmHg, unreacted epoxybutane was removed, and an 8.2 mass% aqueous solution of trisodium ethylenediaminetetraacetate trihydrate was added from pressure inlet 2 of C13 at a rate of 0.14 kg / hr.
[0129] In the above melt-kneading operation, the mixing ratio of the monofunctional epoxy compound (B) was 22.7 parts by mass relative to 100 parts by mass of EVOH (A). 0.78 μmol / g of zinc ions (F) was added in terms of moles relative to the mass of EVOH (A). The ratio (E / F) of the number of moles of the catalyst deactivator (E) to the number of moles of the zinc ions (F) was 3.3.
[0130] The internal pressure of the vent 3 was reduced to 20 mmHg, and moisture was removed to obtain modified EVOH (C). The MFR of the modified EVOH (C) was 5 g / 10 min (190° C., under a load of 2160 g), and the melting point was 109° C. The zinc ion (F) content was 46 ppm (0.70 μmol / g), and the alkali metal salt content was 168 ppm (7.1 μmol / g) in terms of metal elements [sodium: 160 ppm (6.9 μmol / g), potassium: 8 ppm (0.2 μmol / g)].
[0131] The chemical structure of the modified EVOH (C) thus obtained, modified with epoxybutane, was determined by trifluoroacetylating the modified EVOH (C) and then performing NMR measurement according to the procedure described in Patent Document 1. As a result, the ethylene content of the modified EVOH (C) produced in Example 2 was 44 mol %, and the content of the structural unit (I) was 7.0 mol %.
[0132] Using the modified EVOH (C) thus obtained, a single layer film and a multilayer film were produced and evaluated in the same manner as in Example 1. The results are summarized in Tables 1 to 3.
[0133] Example 3 In Example 2, pellets of EVOH {acetic acid content 53 ppm, sodium content 11 ppm (metal element equivalent), potassium content 8 ppm (metal element equivalent), phosphoric acid compound content 20 ppm (phosphate radical equivalent value)} with ethylene content 32 mol%, saponification degree 99.8 mol%, intrinsic viscosity 0.096 L / g, MFR = 8 g / 10 min (190 ° C, under 2160 g load) were used as raw EVOH pellets, and modified EVOH (C) was obtained in the same manner as in Example 2, except that the addition rate of the catalyst deactivator (E) solution was changed to 0.15 kg / hr. Using the modified EVOH (C) thus obtained, monolayer films and multilayer films were produced and evaluated in the same manner as in Example 1. The results are summarized in Tables 1 to 3.
[0134] Example 4 A modified EVOH (C) was obtained in the same manner as in Example 1, except that the addition rate of the catalyst solution (D) was changed to 0.11 kg / hr in Example 1. Using the modified EVOH (C) thus obtained, a single layer film and a multilayer film were produced and evaluated in the same manner as in Example 1. The results are summarized in Tables 1 to 3.
[0135] Comparative Example 9 A modified EVOH (C) was obtained in the same manner as in Example 1, except that the addition rate of the catalyst solution (D) was changed to 0.04 kg / hr in Example 1. Using the modified EVOH (C) thus obtained, a single layer film and a multilayer film were produced and evaluated in the same manner as in Example 1. The results are summarized in Tables 1 to 3.
[0136] Example 6 A modified EVOH (C) was obtained in the same manner as in Example 1, except that the addition rate of the catalyst deactivator (E) solution was changed to 0.22 kg / hr in Example 1. Using the modified EVOH (C) thus obtained, a single layer film and a multilayer film were produced and evaluated in the same manner as in Example 1. The results are summarized in Tables 1 to 3.
[0137] Comparative Example 10 A modified EVOH (C) was obtained in the same manner as in Example 1, except that the addition rate of the catalyst solution (D) was changed to 0.04 kg / hr and the addition rate of the catalyst deactivator (E) solution was changed to 0.32 kg / hr. Using the modified EVOH (C) thus obtained, a single layer film and a multilayer film were produced and evaluated in the same manner as in Example 1. The results are summarized in Tables 1 to 3.
[0138] Comparative Example 11 100 parts by mass of hydrous pellets (moisture content: 130% (dry basis): 57% (wet basis)) made of an ethylene-vinyl alcohol copolymer having an ethylene content of 32 mol%, a saponification degree of 99.6 mol%, and an intrinsic viscosity of 0.0882 L / g were immersed and stirred in 370 parts by mass of an aqueous solution containing 0.1 g / L of acetic acid and 0.88 g / L of potassium dihydrogen phosphate at 25° C. for 6 hours. The obtained pellets were dried at 105° C. for 20 hours to obtain dried EVOH pellets. The dried EVOH pellets had a potassium content of 160 ppm (metal element equivalent), an acetic acid content of 53 ppm, a phosphoric acid compound content of 400 ppm (phosphate radical equivalent), and an alkaline earth metal salt (Mg salt or Ca salt) content of 0 ppm.
[0139] A modified EVOH (C) was obtained in the same manner as in Example 1, except that the thus obtained dry EVOH pellets were used as EVOH (A). Using the thus obtained modified EVOH (C), a single layer film and a multilayer film were produced and evaluated in the same manner as in Example 1. The results are summarized in Tables 1 to 3.
[0140] Example 9 100 parts by mass of hydrous pellets (moisture content: 130% (dry base): 57% (wet base)) made of an ethylene-vinyl alcohol copolymer having an ethylene content of 32 mol%, a saponification degree of 99.6 mol%, and an intrinsic viscosity of 0.0882 L / g were immersed and stirred in 370 parts by mass of an aqueous solution containing 0.1 g / L of acetic acid and 0.022 g / L of potassium dihydrogen phosphate at 25° C. for 6 hours. The obtained pellets were dried at 105° C. for 20 hours to obtain dried EVOH pellets. The dried EVOH pellets had a potassium content of 4 ppm (metal element equivalent), an acetic acid content of 53 ppm, a phosphoric acid compound content of 10 ppm (phosphate radical equivalent), and an alkaline earth metal salt (Mg salt or Ca salt) content of 0 ppm.
[0141] The thus obtained dry EVOH pellets were used as EVOH (A), and modified EVOH (C) was obtained in the same manner as in Example 1, except that the addition rate of the catalyst solution (D) was changed to 0.11 kg / hr and the addition rate of the catalyst deactivator (E) solution was changed to 0.08 kg / hr. Using the thus obtained modified EVOH (C), monolayer films and multilayer films were produced and evaluated in the same manner as in Example 1. The results are summarized in Tables 1 to 3.
[0142] Comparative Example 8 A modified EVOH (C) was obtained in the same manner as in Example 1, except that the addition rate of the catalyst solution (D) was changed to 0.01 kg / hr in Example 1. Using the modified EVOH (C) thus obtained, a single layer film and a multilayer film were produced and evaluated in the same manner as in Example 1. The results are summarized in Tables 1 to 3.
[0143] Example 11 A modified EVOH (C) was obtained in the same manner as in Example 1, except that the catalyst deactivator (E) was changed to a 4.9 mass% aqueous solution of sodium acetate. Using the modified EVOH (C) thus obtained, a single layer film and a multilayer film were produced and evaluated in the same manner as in Example 1. The results are summarized in Tables 1 to 3.
[0144] Comparative Example 1 28 parts by mass of zinc acetylacetonate monohydrate was mixed with 957 parts by mass of 1,2-dimethoxyethane to obtain a mixed solution. 15 parts by mass of trifluoromethanesulfonic acid was added to the obtained mixed solution while stirring to obtain a catalyst solution (D). The catalyst solution (D) contains 1 mole of trifluoromethanesulfonic acid per mole of zinc acetylacetonate monohydrate.
[0145] A modified EVOH (C) was obtained in the same manner as in Example 1, except that the catalyst solution (D) was added at a rate of 0.22 kg / hr. Using the modified EVOH (C) thus obtained, a single-layer film and a multilayer film were produced in the same manner as in Example 1, and evaluated. The results are summarized in Tables 1 to 3. Although the amount of zinc ions (F) contained in the modified EVOH (C) was three times or more that of Example 1, the content of the structural unit (I) was the same as that of Example 1. This shows that a larger amount of zinc ions (F) was required compared to the examples. The number of moles of sulfonate ions contained in the modified EVOH (C) was 1 time the number of moles of zinc ions (F).
[0146] Comparative Example 2 5 kg of the raw material pellets as in Example 2 were placed in a polyethylene bag. A catalyst solution (D) prepared by dissolving 27.44 g (0.125 mol) of zinc acetate dihydrate and 15 g (0.1 mol) of trifluoromethanesulfonic acid in 500 g of water was added to the EVOH in the bag. The EVOH to which the catalyst solution had been added as described above was heated at 90°C for 5 hours with the bag closed while occasionally shaking, so that the EVOH was impregnated with the catalyst solution (D). The obtained EVOH was vacuum dried at 90°C to obtain EVOH pellets containing zinc ions (F) and sulfonate ions.
[0147] As EVOH (A), a pellet mixture was used in which 90 parts by mass of the raw EVOH pellets were dry-blended with 10 parts by mass of the EVOH pellets containing zinc ions and sulfonate ions. A modified EVOH (C) was obtained in the same manner as in Example 2, except that the thus obtained EVOH (A) was used. Using the thus obtained modified EVOH (C), a single layer film and a multilayer film were produced and evaluated in the same manner as in Example 1. The results are summarized in Tables 1 to 3. The number of moles of sulfonate ions contained in the modified EVOH (C) was 0.8 times the number of moles of zinc ions (F).
[0148] Comparative Example 3 In Example 1, monolayer films and multilayer films were produced and evaluated in the same manner as in Example 1 using the dried EVOH pellets before being fed into the extruder. The results are summarized in Tables 1 to 3. The bending resistance was measured after bending the film 25 times, 30 times, 35 times, 40 times, 50 times, 60 times, 80 times, and 100 times.
[0149] Comparative Example 4 In Example 2, using the raw material EVOH pellets before impregnation with the catalyst solution (D), a single layer film and a multilayer film were produced and evaluated in the same manner as in Example 1. The results are summarized in Tables 1 to 3. The bending resistance was measured in the same manner as in Comparative Example 3.
[0150] Comparative Example 5 A modified EVOH (C) was obtained in the same manner as in Example 1, except that the feeding of the catalyst solution (D) and the catalyst deactivator (E) was stopped. Using the modified EVOH (C) thus obtained, a single layer film and a multilayer film were produced and evaluated in the same manner as in Example 1. The results are summarized in Tables 1 to 3.
[0151] Comparative Example 6 In Example 2, instead of using a pellet mixture obtained by dry-blending EVOH pellets containing zinc ions and sulfonate ions with the raw EVOH pellets, only the raw EVOH pellets were used, and the feeding of the catalyst deactivator (E) was stopped, so that a modified EVOH (C) was obtained in the same manner as in Example 1. Using the modified EVOH (C) thus obtained, a single layer film and a multilayer film were produced and evaluated in the same manner as in Example 1. The results are summarized in Tables 1 to 3.
[0152] Comparative Example 7 A modified EVOH (C) was obtained in the same manner as in Comparative Example 1, except that the catalyst solution (D) was added at a rate of 0.06 kg / hr in Comparative Example 1. Using the modified EVOH (C) thus obtained, a single layer film and a multilayer film were produced and evaluated in the same manner as in Example 1. The results are summarized in Tables 1 to 3.
[0153] [Table 1]
[0154] [Table 2]
[0155] [Table 3]
[0156] Example 12 - Manufacturing of resin composition pellets 80 parts by mass of unmodified EVOH having an ethylene content of 32 mol%, a saponification degree of 99.9 mol%, a melt flow rate (190°C, under a load of 2160 g) of 1.6 g / 10 min, and a melting point of 183°C, and 20 parts by mass of the modified EVOH (C) obtained in Example 1 were dry blended to obtain mixed pellets. The mixed pellets were extruded using a 30 mmφ twin-screw extruder (Japan Steel Works, Ltd. TEX-30SS-30CRW-2V) under conditions of a barrel temperature of 200°C, a screw rotation speed of 300 rpm, and an extrusion resin amount of 25 kg / hour, and then pelletized, followed by hot air drying at 80°C for 16 hours to obtain resin composition pellets. The phosphoric acid compound content (in terms of phosphoric acid radicals), acetic acid content, and Na ion content (in terms of metal elements) of the obtained resin composition were measured to be 40 ppm, 250 ppm, and 160 ppm, respectively. The melt flow rate of the resin composition (190° C., under a load of 2160 g) was 1.9 g / 10 min.
[0157] -Oxygen transmission rate measurement The resin composition thus obtained was used to obtain a monolayer film having a thickness of 25 μm in the same manner as in (a) of Example 1. The oxygen transmission rate of the obtained monolayer film was measured in the same manner as in (b) of Example 1, and the oxygen transmission rate was 0.5 cc 20 μm / m 2 The gas barrier properties were excellent, with a gas barrier strength of 1000 MPa (100 MPa) per day atm.
[0158] - Young's modulus measurement The monolayer film was conditioned for 7 days under an atmosphere of 23°C and 50% RH, and then cut into strips of 15 mm width. The film samples were used to measure Young's modulus using a Shimadzu Autograph AGS-H model under conditions of a chuck distance of 50 mm and a tensile speed of 5 mm / min. The measurements were performed on 10 samples each, and the average value was calculated. Young's modulus was 180 kgf / mm 2 It was.
[0159] -Measurement of tensile yield strength and tensile elongation at break The monolayer film was conditioned for 7 days under an atmosphere of 23°C and 50% RH, and then cut into strips of 15 mm width. The film samples were used to measure the tensile strength at yield and the tensile elongation at break using a Shimadzu Autograph AGS-H model under conditions of a chuck distance of 50 mm and a tensile speed of 500 mm / min. The measurements were carried out for 10 samples each, and the average values were calculated. The tensile strength at yield and the tensile elongation at break were 6.5 kgf / mm 2 and 310%.
[0160] Haze measurement Using the monolayer film, the haze was measured in the same manner as in (c) of Example 1. The haze was 0.1%, indicating very good transparency.
[0161] -Evaluation of bending resistance The monolayer film was used to evaluate the flex resistance in the same manner as in (d) of Example 1. As a result, Np1 was 90 times, indicating excellent flex resistance.
[0162] -Evaluation of stretchability of monolayer film The monolayer film was placed in a pantograph-type biaxial stretching device manufactured by Toyo Seiki Seisakusho Co., Ltd., and simultaneously biaxially stretched at a stretch ratio ranging from 2.0×2.0 to 5.0×5.0 at 100° C., varying the stretch ratio by increments of 0.25×0.25. The maximum stretch ratio at which good stretching without tearing was possible was 4.0×4.0, and the stretched film had no unevenness or localized thickness deviation.
[0163] Interlayer adhesion test The resulting resin composition was used to obtain a multilayer film in the same manner as in (g) of Example 1, and the peel strength was measured.
Claims
1. A resin composition comprising a modified ethylene-vinyl alcohol copolymer (C) containing 5.0 to 40 mol % of a structural unit (I) represented by the following formula (I) and having an ethylene content of 5 to 55 mol %, and zinc ions (F), the content of zinc ions (F) being 0.05 to 1.0 μmol / g, and the total content of polymer compounds and additives other than the modified ethylene-vinyl alcohol copolymer (C) being 10 mass % or less. 【Chemistry 1】 (In formula (I), R 1 , R 2 , R 3 and R 4 each independently represents a hydrogen atom, an aliphatic hydrocarbon group having 1 to 6 carbon atoms, an alicyclic hydrocarbon group having 3 to 6 carbon atoms, or a phenyl group, the aliphatic hydrocarbon group, the alicyclic hydrocarbon group, and the phenyl group each optionally having a hydroxyl group, an alkoxy group, a carboxyl group, or a halogen atom; R 3 and R 4 may be bonded to
2. The resin composition according to claim 1, further comprising an alkali metal ion (G), and a molar ratio (G / F) of the alkali metal ion (G) to the zinc ion (F) is 5 to 80.
Citation Information
Patent Citations
Manufacturing method for modified ethylene-vinyl alcohol copolymer
JP2003327619A
Injection-molded article and injection molding method
JP2004161895A
Modified polyvinyl acetal resin
JP2009001631A
Modified ethylene−vinyl alcohol copolymer and method for the production thereof
WO2002092643A1
Resin composition and multi-layer structures
WO2003072653A1